Oligonucleotides as a Novel Therapeutic Approach: An Innovative Area for Drug Delivery in Neurological Disorders - Yasir Qasim Almajidi; Rana Kadum Muslim; Yaseen T. khalf (Al-Mustansiriyah Journal of Pharmaceutical Sciences)
RNA-based therapeutics have emerged as one of the most potent therapeutic options used for the modulation of gene/protein expression and gene editing with the potential to treat neurodegenerative diseases. However, the delivery of nucleic acids to the central nervous system (CNS) by the systemic route, remains a major hurdle.